Defective cortical drive to muscle in Parkinson's disease and its improvement with levodopa - Salenius, Stephan; Avikainen, Sari; Kaakkola, Seppo; Hari, Riitta; Brown, Peter (Brain (London, England : 1878), 2002)
We recorded whole-scalp magnetoencephalographic (MEG) signals simultaneously with surface electromyographic (EMG) activity from eight patients with Parkinson's disease after withdrawal and reinstatement of treatment with levodopa. Variations were seen in the coherence between the forearm extensor EMG and the MEG signal originating near or in the hand region of the primary motor cortex. As a group, the parkinsonian patients withdrawn from levodopa showed a reduction in the coherence at 15-30 Hz and 35-60 Hz, and a further three untreated patients had abnormally strong MEG-EMG coherence at 5-12 Hz compared with when medicated or with eight healthy age-matched control subjects. We conclude that the basal ganglia have a specific effect on the temporal organization of motor cortical activity during voluntary tonic contraction. Abnormalities in this aspect of basal ganglia function may directly contribute to bradykinesia and weakness in Parkinson's disease.